Investment Of Stock In Increasing The Financial Performance Of Pt Goto Gojek Toko Pedia, Tbk And Pt Bukalapak, Tk (Comparative Study And Perspective Of Generation Z Investors In The City Of Palembang) - Pangaribuan, Andhini Aprilia; Harahap, Lily Rahmawati; Aryanti, Rahmi; Kusnan, Kusnan (Journal of Management, Economic, and Accounting, 2025)
This study investigates the impact of stock investment activities on the financial performance of PT GoTo Gojek Tokopedia Tbk and PT Bukalapak.com Tbk, with a specific focus on Generation Z investors in Palembang City. Employing a mixed-methods research design, the study utilizes both quantitative and qualitative data. Quantitative data, derived from the companies' financial statements and historical stock prices, were analyzed using relevant financial ratios. Qualitative data were gathered through questionnaires administered to 100 Generation Z respondents in Palembang City who express an interest in stock investment. An Independent Samples t-test was conducted to determine statistically significant differences in financial ratios between the two companies. The findings indicate a significant relationship between stock activity and the financial performance of both PT GoTo Tbk and PT Bukalapak.com Tbk. While the profit, solvency, and activity ratios did not reveal statistically significant differences between the two entities, the liquidity ratio demonstrated a significant variation. Furthermore, the study reveals a high level of interest in stock investment among Generation Z in Palembang City; however, a considerable portion of this demographic has not actively invested due to perceived financial constraints and limited knowledge regarding investment practices.